Detailed description and analysis of the cross‐coupling magnetic saturation on permanent magnet synchronous motor. Issue 17 (19th October 2018) - Shi, Yu; Chai, Jianyun; Sun, Xudong; Mu, Shujun
Abstract : Permanent‐magnet synchronous motor (PMSM) has obtained more attention, acquired more applications, and received great reputation due to its high torque density and simple structure. While exploiting its high torque capability, PMSM's control strategy faces great challenge at high overload scenario due to core‐saturation effect. This study presents a detailed physical description and analysis on the effect of cross‐coupling magnetic saturation in PMSM. Applying the conventional i d = 0 control strategy on a 1.5 MW surface mounted permanent‐magnet synchronous generator, this study discusses the cause and influence of cross‐coupling effect, presents the unbalanced magnetic permeance between direct ‐( d ‐) and quadrature‐( q ‐)axis magnetic circuit. Either d ‐ or q ‐axis electromotive force (mmf) would generate both d ‐ and q ‐axis flux, especially those induced by permanent magnets. Then a permeance‐fixed finite‐element analysis is applied to separate the influence between permanent magnets and armature current. Finally, this study proposes a revised maximum‐torque‐per‐ampere trajectory for surface‐PMSM at high overload situation.